Modeling the Effects of Bus Stops on Bicycle Traffic Flow by Cellular Automata. (2nd September 2018) - Huang, Zhaoguo; Guo, Xiucheng; Zhang, Chunbo; Zhang, Hongying
Abstract : Since currently huge traffic demands for public bus and bicycles exist in the majority of cities of China, it is highly likely that the bus stop has undeniable impacts on the bicycle flow that is close to the bus stop. In this paper, we proposed the test in several bicycle paths beside bus stops in Nanjing and aimed at exploring the specific effects of bus stop on the bicycle flow nearby. We assumed there were two such effects: space restriction and pedestrian conflicts. Further, we built up a cellular automation (CA) model to study the feature of these effects and find out not only the outcome of these two effects, but also the inner correlation between them.